Strategic Planning as an Alternative to Avoid the Closure of SMEs in Times of Pandemic. Case: Municipality of Garzón, Department of Huila - Reyes, Nelson (Sociedad y Economía, 2023)
COVID-19, which has become a worldwide problem, has affected, first, the whole of humanity, producing a health crisis; and second, the global economy. This research deals with the economic and social effects of Colombian SMEs and how the situation of financial closure or bankruptcy can be overcome. It is estimated that during the pandemic in Colombia, in 2020, 3.9 million jobs were lost, GDP decreased, and exports decreased. An analysis was carried out to propose strategic planning as a method to avoid the definitive closure of companies. A sample was taken in the municipality of Garzón, department of Huila. From the analysis of the results, it stands out that businessmen who use strategic planning can decrease the level of influence of companies in their internal processes and resources. In conclusion, it is evident that strategic management is a key process for the survival of SMEs.